2014
DOI: 10.1007/s13361-014-0962-4
|View full text |Cite
|
Sign up to set email alerts
|

Label Scrambling During CID of Covalently Labeled Peptide Ions

Abstract: Covalent labeling along with mass spectrometry is finding more use as a means of studying the higher order structure of proteins and protein complexes. Diethylpyrocarbonate (DEPC) is an increasingly used reagent for these labeling experiments because it is capable of modifying multiple residues at the same time. Pinpointing DEPC-labeled sites on proteins is typically needed to obtain more resolved structural information, and tandem mass spectrometry after protein proteolysis is often used for this purpose. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Significant neutral losses are also observed in CID of peptides modified by carbenes, making it difficult to pinpoint modification sites [50]. Another issue observed with a subset of DEPC-labeled peptides is the possibility of the label to “scramble” from one site on a peptide to another during CID, presumably due to an intramolecular nucleophilic attack during the CID process [94]. In each of the cases in which CID provided incomplete or misleading information about modification sites, electron transfer dissociation (ETD) was successfully used to correct the problem.…”
Section: Using Covalent Labeling With Mass Spectrometry Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant neutral losses are also observed in CID of peptides modified by carbenes, making it difficult to pinpoint modification sites [50]. Another issue observed with a subset of DEPC-labeled peptides is the possibility of the label to “scramble” from one site on a peptide to another during CID, presumably due to an intramolecular nucleophilic attack during the CID process [94]. In each of the cases in which CID provided incomplete or misleading information about modification sites, electron transfer dissociation (ETD) was successfully used to correct the problem.…”
Section: Using Covalent Labeling With Mass Spectrometry Detectionmentioning
confidence: 99%
“…In each of the cases in which CID provided incomplete or misleading information about modification sites, electron transfer dissociation (ETD) was successfully used to correct the problem. In fact, it has been argued that ETD generally provides improved identification and quantitation of labeled sites produced during oxidative and DEPC labeling experiments [50, 94, 95].…”
Section: Using Covalent Labeling With Mass Spectrometry Detectionmentioning
confidence: 99%
“…Figure 4 compares the rearrangement percentages for sequence 11 as a function of charge state. In its +2 charge state (black), sequence 11 displays the highest rearrangement average (18%, taking into account the CID products [y 13 + 80], [y 11 + 80], and [y 9 + 80]). Adding a third proton (red) leads to a near elimination of rearrangement fragments, with a weak [y 10 + 80] being the only rearrangement product (rearrangement ratio = 2%).…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…Whereas phosphate group loss decreases the amount of information obtained, even more troubling is the possibility of phosphosite scrambling (Scheme C), which can lead to erroneous phosphosite localization. The observation that phosphopeptides can undergo an intramolecular transfer during in‐trap CID was most notably observed by Palumbo and Reid, and since then, Reid and others have attempted to determine how residue identity, activation energy, and activation timescale contribute to the degree of phosphate group rearrangement . On the one hand, some proteomics studies have suggested that phosphate group scrambling is merely a minor problem, minimally affecting sequencing efforts (<1% phosphopeptides producing incorrect sequences) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation